After-Effects of Thixotropic Maneuvers on Chest Wall and Compartmental Operational Volumes of Healthy Subjects Using Optoelectronic Plethysmography - Lima, Illia Nadinne Dantas Florentino; Sarmento, Antonio; Goes, Maria Clara; Mazzuca, Enrico; Lomauro, Antonella; Reid, W. Darlene; Aliverti, Andrea; Fregonezi, Guilherme Augusto De Freitas (Frontiers in Physiology, 2019)
The volumes assessed by optoelectronic plethysmography (OEP) and based on a three-compartmental model provide an accurate breath-by-breath index of expiratory and inspiratory (ribcage muscles and diaphragm) muscle length. Thus, after performing thixotropic maneuvers, OEP may also provide evidence regarding the history-dependent properties of these muscles. We studied the after-effects of different thixotropic conditionings on chest wall and compartmental operational volumes of twenty-eight healthy subjects (25.5±2.2 years, FVC%pred 94.8±5.5, and FEV1%pred 95.5±8.9) using OEP. Conditionings were composed of inspiratory or expiratory contractions performed from total lung capacity (TLC) or residual volume (RV). The study protocol was composed of three consecutive contractions of the same maneuver, with 60s of spontaneous breathing in between, and after-effects were studied in the first seven respiratory cycles of each contraction. Cumulative effects were also assessed by comparing the after-effects of each thixotropic maneuver. Inspiratory contractions performed from both TLC and RV acutely increased end-inspiratory chest wall volumes (all p<0.0001), mainly on both upper and lower ribcage compartments (i.e. non-diaphragmatic inspiratory muscles and diaphragm, respectively); while, expiratory contractions from RV decreased chest wall volumes (p<0.0001) by reducing the upper ribcage and abdominal volumes (all p<0.0001). The response of the thixotropic maneuvers did not present a cumulative effect. In healthy, the use of the three-compartmental model through OEP allows a detailed assessment of the diaphragm, inspiratory and expiratory muscle thixotrophy. Furthermore, specific conditioning maneuvers led to thixotropy of the inspiratory ribcage, diaphragm and expiratory muscles.